Executive function deficits in adults with childhood‐onset type 1 diabetes mellitus: Evidence from Wisconsin card sorting test performance - Jing He; Wenjing Zou; Hongyu Du; Songzhuzi Liu; Xia Li; Zhiguang Zhou; Xiongzhao Zhu (Journal of Diabetes Investigation)
ABSTRACT Background Executive functions (EFs) are important for the Type 1 diabetes mellitus (T1DM) self‐care perspective. This study aimed to investigate whether patients with T1DM have poorer EFs than healthy controls (HCs) and whether there are differences in EFs between childhood‐onset and adult‐onset T1DM. Methods This study included 94, 110, and 100 participants with childhood‐onset and adult‐onset T1DM and HCs, respectively. All participants completed the Wisconsin Card Sorting Test to assess EFs. The Chinese version of the WAIS and BDI‐II were performed to determine IQ and emotion in all participants. Results The childhood‐onset group made lower scores of WCST total errors (P = 0.015), perseverative errors (P = 0.038) than the HC group, and the adult‐onset group made lower scores of WCST total errors (P = 0.025) than the HC group. In the diabetes group, after controlling diabetes duration, the childhood‐onset group made significantly higher scores of WCST total errors (P = 0.040), perseverative errors (P = 0.038), and non‐perseverative errors (P = 0.013). In the childhood‐onset group, perseverative errors were significantly associated with duration of T1DM (β = −0.24, t = −2.34, P = 0.021), and the history of severe hypoglycemia affects the non‐perseverative errors(β = −0.26, t = −2.55, P = 0.013). Conclusions T1DM is associated with EF decrements, and there are differences in EFs between childhood‐onset and adult‐onset T1DM. These findings indicate that we should consider detecting and intervening in EF deficits in the T1DM population according to the age of onset.